2014
DOI: 10.2147/oajsm.s41655
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body cryotherapy: empirical evidence and theoretical perspectives

Abstract: Whole-body cryotherapy (WBC) involves short exposures to air temperatures below −100°C. WBC is increasingly accessible to athletes, and is purported to enhance recovery after exercise and facilitate rehabilitation postinjury. Our objective was to review the efficacy and effectiveness of WBC using empirical evidence from controlled trials. We found ten relevant reports; the majority were based on small numbers of active athletes aged less than 35 years. Although WBC produces a large temperature gradient for tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 48 publications
2
97
0
11
Order By: Relevance
“…The reported effects of WBC are similar to those of CWI including tissue temperature reduction and reduction in markers for muscle damage and inflammation. Bleakley et al (2014) recently reviewed the efficacy and effectiveness of these claims using 10 relevant controlled studies and found most of the claims appear to have some merit. However, comparisons were not made to data regarding CWI as being the current standard in cryotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The reported effects of WBC are similar to those of CWI including tissue temperature reduction and reduction in markers for muscle damage and inflammation. Bleakley et al (2014) recently reviewed the efficacy and effectiveness of these claims using 10 relevant controlled studies and found most of the claims appear to have some merit. However, comparisons were not made to data regarding CWI as being the current standard in cryotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Это иллюстрируется материалами научных исследований посвященных спор-тивному применению криотерапевтической технологии [7,[9][10][11][12][13][14][15].…”
Section: постановка задачиunclassified
“…Результаты математического моделирования про-цесса охлаждения поверхности кожи в криотерапевти-ческих комплексах и холодной воде согласуются с выво-дами зарубежных исследователей [9][10][11][12][13][14][15]. В отдельных случаях процедуры с использованием криогенных газо-вых сред обеспечивают крайне низкий лечебный резуль-тат.…”
Section: обсуждение результатовunclassified
See 2 more Smart Citations